2021
DOI: 10.1002/joe.22131
|View full text |Cite
|
Sign up to set email alerts
|

Building a multilevel integrated framework of ambidexterity: The role of dynamically changing environment and human capital management in the performance of Greek firms

Abstract: The purpose of this study is to investigate the serially mediating mechanisms of human capital management practices and organizational ambidexterity, expressed by exploration and exploitation, in the relationship between environmental dynamism and organizational performance, expressed by creativity and productivity. The study is based on 1,183 employees working in 83 Greek private sector firms. By applying multi‐level structural equation modeling, the findings show that the dynamically changing environment has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 38 publications
3
8
0
Order By: Relevance
“…For example, Kauppila and Tempelaar (2016) highlight the significant role of psychological capital, including efficacy, in the capacity of individuals for ambidextrous behavior, because high levels of efficacy promotes ambitious goal-setting and greater effort, thus helping individuals to manage the challenges associated with paradoxical orientations and conflicting work demands. This is consistent with the findings of Katou (2021), with one difference in that Katou shows that ambidexterity is affected by human capital, which is itself positively influenced by the dynamically changing environment. This indicates the importance of acquiring and strengthening capabilities for public sector organizations that enable individuals and managers to be effective in both optimization and innovation and gain mastery in dealing with existing tensions (Gieske et al, 2019) and the changing environment to achieve higher productivity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For example, Kauppila and Tempelaar (2016) highlight the significant role of psychological capital, including efficacy, in the capacity of individuals for ambidextrous behavior, because high levels of efficacy promotes ambitious goal-setting and greater effort, thus helping individuals to manage the challenges associated with paradoxical orientations and conflicting work demands. This is consistent with the findings of Katou (2021), with one difference in that Katou shows that ambidexterity is affected by human capital, which is itself positively influenced by the dynamically changing environment. This indicates the importance of acquiring and strengthening capabilities for public sector organizations that enable individuals and managers to be effective in both optimization and innovation and gain mastery in dealing with existing tensions (Gieske et al, 2019) and the changing environment to achieve higher productivity.…”
Section: Discussionsupporting
confidence: 90%
“…Ambidexterity is a vital mechanism (Affum-Osei et al 2020) that creates new capacities for the organization while strengthening other beneficial relationships. The overall model of the effect of psychological capital and ambidexterity on organizational performance is consistent with Katou (2021), who found that human capital management practices constitute an antecedent of organizational ambidexterity and organizational performance constitutes a consequence.…”
Section: Discussionsupporting
confidence: 84%
“…This study will also discuss the factors that impact research in knowledge management. Indeed, this study can significantly help formulate future research agendas for the journal, and its findings can inform and guide new research in the field, thereby reaffirming the importance of pertinent building blocks such as agility (Ong and Tan, 2022), ambidexterity (Katou, 2021; Rossi et al , 2019), culture (Arora and Patro, 2021; Kimble, 2020; Memon et al , 2020; Sandberg and Abrahamsson, 2022; Schultz, 2022; Varshney, 2020), entrepreneurship (Brockman et al , 2021; Hussain et al , 2021; Liao et al , 2022; Nicotra et al , 2018; Orlando et al , 2021; Scuotto et al , 2020a; Sharma et al , 2021; Shi and Weber, 2021), externalities (Sutarto et al , 2022), innovation (Papa et al , 2021; Usai et al , 2020), intellectual capital (Carayannis et al , 2014; Paoloni et al , 2020; Schiavone et al , 2014), leadership (Islam et al , 2021; Lacan, 2021), quality management (Abd Samad and Othman, 2022) and technology advancement (Campanella et al , 2020; Del Giudice et al , 2019; Di Vaio et al , 2020; Sajid et al , 2022) in future efforts to develop and extend understanding of knowledge management (Caputo et al , 2021; Rossi et al , 2020; Scuotto et al , 2020B) for organizational excellence (Kopelman, 2022). More importantly, the findings of this study will assist the editorial board of JKM in curating and shaping future directions of the journal around the thematic clusters, which will, in turn, help develop the field of knowledge management.…”
Section: Introductionmentioning
confidence: 65%
“…Previous studies have mostly focused on the link between ambidextrous leadership and team innovation (Zacher and Rosing, 2015), team performance (Gerlach et al, 2020a, b), innovative work behavior (Usman et al, 2020), organizational excellence (Al-Eida, 2020) and employee innovation (Al-Eida, 2020; Kung et al, 2020). Up to the best knowledge, Its impact on employee creativity has yet to be investigated (Katou, 2021). Second, the current study demonstrates by explaining how ambidextrous leadership affects employee creativity by developing ambidextrous behavior of employees.…”
Section: Ambidextrous Behaviormentioning
confidence: 99%
“…The amount of innovation and creativity that is supported in a firm is influenced by organizational culture. As a result, in order to improve organizational lifecycle excellence, innovation and creativity play a vital role in society (Katou, 2021). Previously, researchers claimed that corporate culture plays an important role in predicting creativity (Taghizadeh and Rahman, 2013).…”
Section: 24mentioning
confidence: 99%